Relationships among birth-month distribution, skeletal age and anthropometric characteristics in adolescent elite soccer players - Hirose, N. (Journal of Sports Sciences, 2009)
The aim of the present study was to clarify relationships among the distribution of birth month, maturation and body size in young soccer players. We therefore examined physical and maturational differences between selected players, who were considered to have higher potential to play soccer at a professional level as decided subjectively by coaches, and unselected players. Participants were 332 elite soccer players (mean age = 12.2 ± 1.5 years; range = 9.1-15.0 years). Participants were divided into six categories (under = U10 to U15), depending on chronological age. Height, body mass skeletal age and maturation difference (skeletal age - chronological age) were compared among four groups (quarter = Q1 to Q4) depending on month of birth. Overall, the distribution of players across the four quarters was skewed such that numbers were greatest in Q1 and smallest in Q4. No significant differences in maturation difference were observed between birth quarters in any age category. On the other hand, except for the U14 age category, there were no significant differences in height between Q4 and Q1 players. However, the height of Q4 players was significantly smaller than those of Q1 in three (U11, U13 and U14, P < 0.01) of six categories when maturation difference was statistically controlled. Our results suggest a clear bias toward quarter of birth and this bias may depend to some extent on differences in individual skeletal age and body size. Individual biological maturation should thus be considered when selecting adolescent soccer players.